Penangkapan Ikan Menggunakan Handline Tuna pada Kegiatan Teaching Factory di Laut Maluku - Karyanto, Karyanto; Purwanto, Yuli; Darondo, Franky Adrian; Takasabare, Erick Octavian; Karendehe, Pedro Gustavo (JURNAL BLUEFIN FISHERIES, 2023)
Bitung Marine and Fisheries Polytechnic is a vocational college that implements Teaching Factory (TEFA) based vocational education. The aim of tefa learning activities is that students can master the skills and technical skills of catching tuna using a handline and knowing the catch. One of the tefa-based activities in the Fishing Engineering Study Program is deep sea fishing using tuna handlines. Activities were carried out during 2 fishing trips in the Maluku Sea using an experimental fishing approach. Data analysis uses qualitative descriptive methods. Analysis was carried out on tuna fishing techniques using handline. Based on research results, tuna fishing is carried out from 05.00-17.00 WITA. The catches obtained were dominated by yellowfin tuna (Thunnus albacores), Trip 1 was 27 fish weighing 865 kg, while trip 2 was 10 fish weighing 375 kg. Cadets gain adequate competency in the field of fishing using handline fishing equipment, and increase their sailing hours.